Assessments for sport and athletic performance - Fukuda, D. H. (Human Kinetics, 2019)
Many scientific sport assessment resources are difficult to understand, can be time consuming to implement, and provide data that are difficult to analyze. Assessments for Sport and Athletic Performance effectively solves those problems in this practical, user-friendly guide to performance-based evaluation.